Thymic Carcinoma Presenting as Disseminated Intravascular Coagulation - Mamatha Siricilla; Jawairia Memon; Robert Avery (Case Reports in Oncological Medicine)
Thymomas and thymic carcinomas are rare tumors, which originate from the epithelial cells of the thymus. We present a case of thymic carcinoma, which presented with DIC as an initial manifestation. DIC improved with corticosteroid treatment and thymic carcinoma was amendable to chemoradiation.